Analisis Kemampuan Literasi Sains Siswa Kelas IX MTs Negeri 1 Lampung Barat Pada Materi Bioteknologi Berbasis Etnosains - Juwita, Ema; Sunyono, Sunyono; Rosidin, Undang (Universitas PGRI Madiun, 2022)
21st century education aims to improve students' scientific literacy skills. The results of the PISA study show that the scientific literacy of Indonesian students is in the low category. The low scientific literacy of students is caused by several factors in the education system, such as the curriculum, teachers, and students themselves. This study aims to describe the scientific literacy ability of Class IX.A students of MTs Negeri 1 West Lampung and the factors that influence it. Information about scientific literacy skills is important to know in order to provide appropriate solutions to the problems faced, especially in the field of scientific literacy. This research is a descriptive research with a combination method (mixed method). The research sample was 28 students who were taken by cluster random sampling technique. The instruments used were scientific literacy test questions and interview guide sheets. The data analysis technique was carried out by giving a score for each student's answer then interpreted into the value and category of scientific literacy achievement and analyzing the results of the interview. Based on the results of the study, it is known that the average value of scientific literacy for Class IX.A students at MTs Negeri 1 Lampung Barat is 36.19 with a low category. The low scientific literacy ability of these students is influenced by several factors, namely low interest in reading, evaluation tools that have not led to the development of scientific literacy, lack of teacher knowledge about scientific literacy, and teaching materials that are able to develop scientific literacy skills.